PENGENDALIAN VEKTOR NYAMUK AEDES AEGYPTI DI RUMAH SAKIT KOTA SURABAYA - Ekalina Atikasari; Lilis Sulistyorini (Universitas Airlangga, 2018)
Vector control is an approach using the basic principles of management and consideration of disease transmission and control. The purpose of vector control is to reduce vector breeding habitats, reduce vector density, inhibit disease transmission, reduce human contact with vectors so that vector-borne disease transmission can be controlled more rationally, effectively and efficiently. This study aims to analyze the effectiveness of Aedes aegypti mosquito control vector in a hospital in Surabaya. The Control carried out by the Hospital is to eradicate Aedes aegypti mosquitoes by installing Ovitrap, Thermal Fogging, Cold Fogging and Spraying. The type of analysis used is descriptive observational. Data collection was carried out in February of 2017 at K3 unit and Environmental Health of Surabaya Hospital. The data used are hospital pest and rodent control report, secondary data aboutnumber of mosquito, number of larvae and number of Aedes aegypti mosquito eggs obtained from unit of K3 and Environmental Health. The conclusions for the hospital are: (1) always report the Aedes aegypti mosquito vector routine every months; (2) eradicating mosquitoes in difficult places such as patient and dense populated areas; (3) based on Regulation of the Minister of Health of the Republic of Indonesia Number 374 / MENKES / PER / III / 2010 concerning Vector Control four of the six tools used in the Hospital have been used